Menjadi Entrepreneur Muda Mengubah Hobi Dan Bakat Menjadi Bisnis - Sabyla Chandra Juniar; Kahlilia Febrianti; Nur Mukholipah; Veta Lidya Delimah Pasaribu (CV. ITTC INDONESIA, 2025)
This community service is carried out at Pelita Bangsa High School with the aim of fostering an entrepreneurial spirit among students. The activities are focused on how students' hobbies and talents can be transformed into creative, innovative, and economically valuable business opportunities. Through an educational approach, training, and mentorship, students are guided to recognize their potentials, design business ideas, and understand the basic steps of simple business management. The expected outcomes are the formation of a young entrepreneurial mindset within the school environment, an increase in students' entrepreneurial skills, and the existence of examples of products or services resulting from the development of students' hobbies and talents that can be commercialized.